1999
DOI: 10.1046/j.1440-1681.1999.03154.x
|View full text |Cite
|
Sign up to set email alerts
|

SELECTIVE EFFECTS OF LOMERIZINE, A NOVEL DIPHENYLMETHYLPIPERAZINE Ca2+ CHANNEL BLOCKER, ON CEREBRAL BLOOD FLOW IN RATS AND DOGS

Abstract: 1. In the present study we examined the effects of a new Ca2+ channel blocker (lomerizine), an antimigraine drug, on cerebral cortical blood flow (CBF) in anaesthetized rats (laser Doppler flowmetry) and on vertebral blood flow in anaesthetized beagle dogs (electromagnetic flowmeter). 2. Lomerizine (1.25-10 mg/kg, p.o.) dose-dependently increased CBF in rats without affecting blood pressure (BP) or heart rate (HR). 3. The plasma concentration of lomerizine (free base) in anaesthetized rats at 30 and 60 min aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Hara et al (1999) have studied in anesthetized rats the effects of lomerizine, a CCB of the piperazine group, on cerebral blood flow by laser Doppler flowmetry and on vertebral blood flow in anesthetized beagle dogs with an electromagnetic flowmeter. They observed that lomerizine (2.5 and 5 mg/kg, intraduodenally) dose-dependently increased vertebral blood flow in dogs without significantly changing BP or HR.…”
Section: Acute Hemodynamic Effects Of Ccbsmentioning
confidence: 99%
“…Hara et al (1999) have studied in anesthetized rats the effects of lomerizine, a CCB of the piperazine group, on cerebral blood flow by laser Doppler flowmetry and on vertebral blood flow in anesthetized beagle dogs with an electromagnetic flowmeter. They observed that lomerizine (2.5 and 5 mg/kg, intraduodenally) dose-dependently increased vertebral blood flow in dogs without significantly changing BP or HR.…”
Section: Acute Hemodynamic Effects Of Ccbsmentioning
confidence: 99%
“…2,34 The resultant increase in cytoplasmic calcium concentrations activates intracellular calcium-dependent signaling processes 35 that may lead to secondary death by apoptotic or necrotic processes. 36 -38 The relatively newly synthesized calcium channel blocker lomerizine, also known as KB-2796, is a diphenylmethylpiperazine compound currently marketed as an antimigraine drug 39 and is in phase II clinical trials for glaucoma. 40,41 Lomerizine is highly selective for L-type channels in the CNS and cerebral arteries and therefore has few peripheral side effects.…”
mentioning
confidence: 99%
“…Oral or intraduodenal administration of this drug induced a dose-dependent and continuous increase in both CBF in rats and VBF in dogs, largely without affecting BP or HR (30). The values obtained for the plasma concentration of lomerizine (free base) in anesthetized rats at 30 and 60 min after the initial administration of 5 mg/kg, p.o.…”
Section: Selective Effects Of Lomerizine On Cerebral Blood Flowmentioning
confidence: 86%
“…Lomerizine has been investigated for its effects on cerebral cortical blood flow (CBF) in anesthetized rats (by laser Doppler flowmetry) and on vertebral blood flow (VBF) in anesthetized beagle dogs (by electromagnetic flowmetry). Oral or intraduodenal administration of this drug induced a dose-dependent and continuous increase in both CBF in rats and VBF in dogs, largely without affecting BP or HR (30). The values obtained for the plasma concentration of lomerizine (free base) in anesthetized rats at 30 and 60 min after the initial administration of 5 mg/kg, p.o.…”
Section: Selective Effects Of Lomerizine On Cerebral Blood Flowmentioning
confidence: 86%